Quantitative and qualitative comparison of gall bladder mucus glycoprotein from patients with and without gall stones. Issue 4 (April 1986) - Harvey, P R; Rupar, C A; Gallinger, S; Petrunka, C N; Strasberg, S M
Abstract : Human gall bladder mucus glycoprotein was isolated by Sepharose 4B gel filtration followed by caesium chloride density gradient ultracentrifugation from four groups: patients with cholesterol gall stones, patients with pigmented stones, patients with complete obstruction of the cystic duct and patients with no biliary tract abnormalities (controls). Mucus glycoprotein concentrations in cholesterol gall stone bile (203 micrograms/ml +/- 199 SD, n = 17), pigment gall stone bile (110 micrograms/ml +/- 77 SD, n = 6) and control gall bladder bile (96 micrograms/ml +/- 98 SD, n = 11) were not significantly different. While bile from patients with complete obstruction of the cystic duct contained significantly higher concentrations of mucus glycoprotein (6220 micrograms/ml +/- 4130, n = 4). In vitro cholesterol nucleation time was not correlated to gall bladder mucus glycoprotein concentrations. Qualitative analysis of the carbohydrate and amino acid composition showed a basic structure typical of mucus glycoproteins in general. It is unlikely that either quantitative or qualitative differences in mucus glycoproteins are responsible for the rapid in vitro nucleation time characteristic of cholesterol gall stone patients.